Hubungan pengetahuan perawat dengan penerapan triase sesuai protokol kesehatan covid-19 di instalasi gawat darurat di brsud kabupaten tabanan: Relationship between nurse knowledge and implementation of triage according to covid-19 health protocol in emergency installation at brsud, tabanan - Sari, Ni Putu Intan Puspa; Yundari, AA Istri Dalem Hana; Azis, Abdul (Stikes Wira Medika Bali, 2021)
Introduction: Knowledge is very important factor in the accurancy of triage implementation in accordance with the COVID-19 health protocol during this pandemic, if the knowledge of nurse is very good, then triage handling in hospitals, especially in the emergency unit, will be maximized. The purpose of this study was to determine the relationship between nurses knowledge relate to triage and application of triage according to the COVID-19 health protocol in the emergency unit. Method: This study uses a descriptive correlational method with a cross-sectional approach. This study with a sample of 37 respondents, the sample was taken using a non-probability sampling technique with purposive sampling. This study uses a reseach instrument, namely aguestionnaire sheet for the knowledge variable and an observation sheet for the application variable, for the knowledge questionnaire a validity test has been carried out at Wangaya Hospital Denpasar on 29 April-7 May 2021, with the results of the validity test of 0,366-0,705 and the results of the realiability test by using alpha cronbach of 0,921. Result: The results of this study indicate that 25 people (67,6%) respondents who have a good level of knowledge and good application of triage, and there are 12 people (32,4%) respondents with a enough level of knowledge and enough application. Based on the spearman rank test, it was obtained with a value that p value = 0.000 <α=0,05, which means that the hypothesis in this study is accepted where statistically the is a relationship between the level of knowledge and the application of triage according to the COVID-19 health protocol. The correlation value on the variable level of knowledge with the application of triage of 0.605 means that it shows the level of a strong relationship between the level of knowedge and the application of the COVID-19 health protocol triage in the IGD BRSUD Tabanan, with the derection of a positive correlation relationship which means that the better the level of knowledge of nurse regarding triage, the better. Also the level of triage compliance in accordance with the COVID-19 protocol. Discussion: The applicaton triage is very important in the proses determining the level of emergency patients, in this case the level of knowlwdge of nurses greatly affects the process of applying triage so as to increase the knowledge of nurses in carrying out triage actions appropriately so that it can be applied properly.